Collective security - Orakhelashvili, Alexander (Oxford : Oxford University Press, 2011)
Collective security is a concept often mentioned but not always well understood. This book provides an overview of the whole collective security system, encompassing the UN and regional organisations. It takes a bottom-up approach to analysing these institutions, their competencies and interactions, focusing on the relevant practice.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Security, International